Two small genera, Ischyroptyx Delucchi and Novitzkyanus Bouček (Hymenoptera: Pteromalidae) new to fauna of Iran. (1st October 2020) - Rahmani, Zahra; Rakhshani, Ehsan; Lotfalizadeh, Hossein; Mokhtari, Azizollah
ABSTRACT: The genera Ischyroptyx Delucchi, 1956 and Novitzkyanus Bouček, 1961 are first recorded from Iran. They are represented by two species, Ischyroptyx ligusticus (Masi, 1922) and Novitzkyanus cryptogaster Bouček, 1961, respectively. First species was collected from Northeast (North Khorasan Province) by sweeping net and the second species was collected from both North East, Central (Isfahan Province) and South Eastern (Kerman Province) parts of Iran, by the Malaise traps. Brief morphological remarks as well as illustrations of the morphological characters are provided for each species.